Effects of Video-Assisted 5E Learning Cycle Instruction on Mathematical Literacy - Annisa Stabita; Sari Herlina (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study aimed to examine the effect of a video-assisted 5E Learning Cycle model on Grade 11 students’ mathematical literacy at SMA Negeri 3 Siak Hulu. A quasi-experimental method with a nonequivalent control group design was employed. The study is timely in a global context, as mathematical literacy is widely recognized as a key 21st-century competency. The population comprised all Grade 11 students at SMA Negeri 3 Siak Hulu in the 2024/2025 academic year. Using purposive sampling, two intact classes were selected: Class XI.3 (n = 35) as the experimental group and Class XI.2 (n = 35) as the control group. Data were collected using pretest and posttest instruments and analyzed through descriptive and inferential statistics. The findings indicated a difference in the mean mathematical literacy scores between the experimental and control groups. Therefore, it can be concluded that video-assisted 5E Learning Cycle instruction had a significant effect on students’ mathematical literacy. This study contributes to the literature by providing evidence on the effectiveness of an innovative, video-supported instructional model and offers practical implications for implementing more effective and sustainable mathematics learning.